Analisis Kebijakan Kurikulum Merdeka Melalui Implementasi Proyek Penguatan Profil Pelajar Pancasila di Sekolah Dasar - Desi Aulia; Hadiyanto; Rusdinal (University of Muhammadiyah Malang, 2023)
Implementing the Pancasila Student Profiles Strengthening Project as a focus in the Merdeka Curriculum has yet to be fully implemented. The study aims to analyze the policy of the Merdeka Curriculum by implementing the Pancasila Student Profiles Strengthening Project in elementary schools. This study employed a qualitative descriptive approach to describe various phenomena and events. The research subjects were taken from 34 students in class IV and three informants, consisting of the head of the school and 2 class teachers who have already implemented the Merdeka Curriculum in primary schools. Research data collected through observations, interviews, and documentation is described. The findings showed that the implementation of the Pancasila Student Profile Strengthening Project through the theme of entrepreneurship could help students to develop the competence and character of the Pancasila Student Profile, namely faith, piety to God Almighty, and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creative. Thus, the Pancasila Student Profiles Strengthening Project is a project-based co-curricular activity designed to strengthen student competence and character under the Pancasila Student Profile in the Merdeka Curriculum.